Ore deposits, magmatism and precambrian geology of Finland: Field trip guidebook ... - Schlöglova, Katerina; Lecumberri-Sanchez, Pilar; Heinrich, Christoph A. (ETH Zurich, 2014)
ISBN:978-3-906031-69-9 ...